PELAKSANAAN EKSEKUSI DENDA TILANG OLEH KEJAKSAAN NEGERI SURAKARTA - Viona Damayanti; Vincentius Patria Setyawan (Sebelas Maret University, 2021)
The Trial Process at the Surakarta District Court and the Execution of Fines for Traffic Violations by the Surakarta District Attorney can be described as follows: to receive payment of ticket fines by the convict who has obtained a decision from the District Court Judge where the trial of this traffic violation case is taking place. The Public Prosecutor was not present directly in the trial process because in principle the trial of this traffic violation case was a minor crime case and the proceedings were fast, and was only attended by a single judge, clerk/substitution clerk and the accused. After the convict receives a verdict from the court judge, he then pays a ticket fine and court costs in accordance with the judge's decision. For the special treasurer of the recipient/depositor, after receiving the Minutes of Submission of Fines and Case Fees and also containing an Order for Submission of Fines/Replacement Fines/and an amount of money for fines and case fees for traffic violations, this then deposits it in the designated state treasury, namely the Office of PT. POS INDONESIA Branch Surakarta or Bank BRI. Furthermore, the special treasurer who receives money for traffic violations and case fees for traffic violations makes a report in the form of a Non-Tax Deposit Letter (SSBP) as proof that the handling of traffic violation cases and all fine money for fines and case fees have been deposited to the state treasury.Keyword: Execution, Fines, Traffic Violations